Keunggulan Bersaing UMKM Berbasis Sumber Daya di Tengah Pandemi Covid-19 - Anfas Anfas; Ida Hidayanti (IPM2KPE, 2022)
This study aims to describe the strategic steps that can be applied by MSMEs, in order to be able to utilize their resources to achieve competitive advantage, especially in conditions of uncertainty, such as the current covid-19 pandemic. The method used in this research is library research. The steps for collecting information and data are carried out in stages, starting from: (i) Design, (ii) Implementation, (iii) Analysis, and (iv) Compiling and writing a review. The results show that in achieving competitive advantage there are many resource variables that influence it. The results showed that the variables of innovation ability and creativity are resources that have a dominant influence on competitive advantage. In addition, another dominant variable that also affects competitive advantage is HR, because HR holds an important key in running the MSE business, including in creating various innovations and creativity. For this reason, the strategic steps that must be taken by MSMEs are to increase innovation and creativity, if they want to survive and be able to compete in any conditions, especially in conditions of uncertainty. Like Darwin's theory of evolution: The Survival of the Fittest, SMEs must be prepared to adapt to changes in the environment that affect business. Keywords: Innovation, Creativity, Competitiveness, Competitive Advantage, Resources, MSME